Enhancement of chemical stability and crystallinity in porphyrin-containing covalent organic frameworks by intramolecular hydrogen bonds - Kandambeth, Sharath; Shinde, Digambar Balaji; Panda, Manas K.; Lukose, Binit; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: covalent organic frameworks; hydrogen bonds; mesoporous materials; porphyrinoids; tautomerism

Mechanosynthesis of imine, beta-ketoenamine, and hydrogen-bonded imine-linked covalent organic frameworks using liquid-assisted grinding - Das, Gobinda; Shinde, Digambar Balaji; Kandambeth, Sharath; Biswal, Bishnu P.; Banerjee, Rahul (Chemical Communications, 2014)
A variety of aromatic amines/hydrazides and aldehydes have been utilized for the construction of crystalline COFs at a faster rate and in high yield, irrespective of their reactivity and solubility using the Liquid-Assisted Grinding (LAG) method.

Bifunctional covalent organic frameworks with two dimensional organocatalytic micropores - Shinde, Digambar Balaji; Kandambeth, Sharath; Pachfule, Pradip; Kumar, Raya Rahul; Banerjee, Rahul (Chemical Communications, 2015)
We report the successful incorporation of bifunctional (acid/base) catalytic sites in the crystalline organocatalytic porous COF (2,3-DhaTph). Due to the presence of acidic (catachol) and basic (porphyrin) sites, 2,3-DhaTph shows significant selectivity, reusability, and excellent ability to perform the cascade reaction.

Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Cobalt-modified covalent organic framework as a robust wateroxidation electrocatalyst - Aiyappa, Harshitha Barike; Thote, Jayshri; Shinde, Digambar Balaji; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry of Materials, 2016)
The development of stable, efficient oxygen evolution reaction (OER) catalyst capable of oxidizing water is one of the premier challenges in the conversion of solar energy to electrical energy, because of its poor kinetics. Herein, a bipyridine-containing covalent organic framework (TpBpy) is utilized as an OER catalyst by way of engineering active Co(II) ions into its porous framework. The as-obtained Co-TpBpy retains a highly accessible surface area (450 m(2)/g) with exceptional stability, even after 1000 cycles and 24 h of OER activity in phosphate buffer under neutral pH conditions with an overpotential of 400 mV at a current density of 1 mA/cm(2). The unusual catalytic stability of Co-TpBpy arises from the synergetic effect of the inherent porosity and presence of coordinating units in the COF skeleton.

Constructing covalent organic frameworks in water via dynamic covalent bonding - Thote, Jayshri; Aiyappa, Harshitha Barike; Kumar, Raya Rahul; Kandambeth, Sharath; Biswal, Bishnu P.; Shinde, Digambar Balaji; Roy, Neha Chaki; Banerjee, Rahul (Iucrj, 2016)
The formation of keto-enamine based crystalline, porous polymers in water is investigated for the first time. Facile access to the Schiff base reaction in water has been exploited to synthesize stable porous structures using the principles of Dynamic Covalent Chemistry (DCC). Most credibly, the water-based Covalent Organic Frameworks (COFs) possess chemical as well as physical properties such as crystallinity, surface area and porosity, which is comparable to their solvothermal counterparts. The formation of COFs in water is further investigated by understanding the nature of the monomers formed using hydroxy and non-hydroxy analogues of the aldehyde. This synthetic route paves a new way to synthesize COFs using a viable, greener route by utilization of the DCC principles in conjunction with the keto-enol tautomerism to synthesize useful, stable and porous COFs in water.

Mechanochemically synthesized covalent organic framework as a proton-conducting solid electrolyte - Shinde, Digambar Balaji; Aiyappa, Harshitha Barike; Bhadra, Mohitosh; Biswal, Bishnu P.; Wadge, Pritish; Kandambeth, Sharath; Garai, Bikash; Kundu, Tanay; Kurungot, Sreekumar; Banerjee, Rahul (Journal of Materials Chemistry A, 2016)
Mechanochemistry has become an increasingly important synthetic tool for a waste-free environment. However, the poor quality of the so-derived materials in terms of their crystallinity and porosity has been their major drawback for any practical applications. In this report, we have for the first time successfully leveraged such characteristics to show that the mechanochemically synthesized bipyridine based covalent organic framework (COF) outperforms its conventional solvothermal counterpart as an efficient solid-state electrolyte in PEM fuel cells. Marking the first such attempt in COFs, a Membrane Electrode Assembly (MEA) fabricated using the mechanochemically synthesized COF was observed to inhibit the fuel crossover and build up a stable Open Circuit Voltage (OCV = 0.93 V at 50 degrees C), thereby establishing itself as an effective solid electrolyte material (with a proton conductivity of 1.4 x 10(-2) S cm(-1)), while the solvothermally synthesized COF proved ineffective under similar conditions.

State-of-the-art catechol porphyrin COF catalyst for chemical fixation of carbon dioxide via cyclic carbonates and oxazolidinones - Saptal, Vitthal; Shinde, Digambar Balaji; Banerjee, Rahul; Bhanage, Bhalchandra M. (Catalysis Science & Technology, 2016)
A highly porous, crystalline catechol porphyrin COF was synthesized and applied as an organocatalyst for the chemical fixation of carbon dioxide to synthesize value-added chemicals such as cyclic carbonates and oxazolidinones under solvent-free and transition-metal-free conditions. The high surface area and the functionalities of the COF catalyst act synergistically to activate the starting material. The 2,3-DhaTph shows excellent activity towards cyclic carbonates at the atmospheric pressure of carbon dioxide. Additionally, this catalytic system is recyclable in nature and provides a higher turnover number than previously reported organocatalysts.